Solusi Intervensi Kemanusiaan Sebagai Penyelesaian Konflik Yang Terjadi Pasca Kudeta Presiden Mursi Di Mesir - Dodik Setiawan Nur Heriyanto (Universitas Islam Indonesia, 2013)
Mohamed Morsi was became Egypt’s first democratically elected president based on Presidential election held in 2012. However, he has been ousted from Presidential office just over one year into his presidency. President Morsi and Muslim Brotherhood leaders were arrested. Egypt’s Minister of Defense was appointed Adly Mansour as interim president until an election could take place based on the announcement of Egypt’s Minister of Defense. This announcement caused several days of bloodshed, since around 600 people were killed in clashes as police broke up protest camps of Morsi supporters. This condition raised international protest and urged immediate humanitarian intervention to end turmoil and save most Egyptians. This paper will analyzed whether or not the need of humanitarian intervention give an effective solution for Egypt’s crises.Keywords : humanitarian, resolution, Egypt